PENGARUH MOTIVASI BELAJAR DAN MINAT BELAJAR MAHASISWA BERDASARKAN LATAR BELAKANG SEKOLAH TERHADAP HASIL BELAJAR MATA KULIAH KONSEP MATEMATIKA II MAHASISWA PGSD UNIVERSITAS BUNG HATTA - Ira Rahmayuni Jusar; Syafni Gustina Sari (PAKAR Pendidikan, 2017)
This study aims to determine the influence of learning motivation and student interest based on the background of the school are students who graduated from high school and vocational school graduates in the mathematics course II of the student learning outcomes are known from the Study Results Sheet (LHS) students. The research method used is quantitative research using expost facto approach. Population in this research is PGSD student of Bung Hatta University class of 2016. The sample was taken as many as 40 students covering 20 students with background from high school and 20 students from school background from SMK. The value of learning motivation and student learning interest obtained from the questionnaire and the value of student learning outcomes obtained from LHS. . Meanwhile, to know the effect of motivation on the results of study used F-test data analysis techniques. In the hypothesis test obtained that high school graduate student obtained F value is 3.603 with probability 0.048 <0.05. Because probabiltasnya less than 0.05 then H0 rejected means there is influence of learning motivation and interest in learning on high school graduate students. For students of SMK graduates obtained the value of F = 0.784 with probability 0.473> 0.05 then H0 accepted means there is no influence of motivation and interest in learning on students who graduate SMK